Willingness to pay for conservation fee of Gunung Santubong National Park / Almisahrezza Saadon - Saadon, Almisahrezza (2015)
National park is one of the environmental resources and for public goods used by people that can gives benefit in wide range ways. Those natural parks have many functions relating to the ecological functions, They also offer recreational purpose to everyone who visits the park. National parks which are plays roles as ecotourism sites can contribute in national income, and at the same time gives an economic impact to society around the area Of national park. Then, it can contribute to the national financial development of the country (Gordon Cessford, 2008)